The Complex Network of Public Policies : An Empirical Framework for Identifying their Relevance in Economic Development - Castaneda, Gonzalo (World Bank, Washington, DC, 2017)
This paper presents an innovative methodology for discovering policies that are consistent with economic development. A development footprint narrative is advanced to suggest that laggard countries can improve their good overall economic performance when tracking policy indicators of more advances but structurally similar economies. This narrative is converted in a workable policy guideline through the use of a complex network of public policies. The main results generated when the model is calibrated with a panel of countries in all income categories for the period 2006-2012 are as follows: (i) public policies are context dependent; (ii) there are different development modes that any country can undertake; (iii) policy interventions within each mode are part of a consistent package and, thus, they should not be implemented in isolation; and (iv) bosting public governance indicators do not seem to be important for the poorest countries of income group 4, but this type of actions are very critical in upper-middle income countries of group 2.